Bedouin folktales from the north of Israel - Rosenhouse, J.; Perets, Yoʼel Shalom (Indiana University Press, 2022)
"Galilee has been a crossroads of cultures, religions, and languages for centuries, as illustrated in fascinating Bedouin folktales, which offer excellent examples of the Arabic narrative tradition of the Middle East. Bedouin Folktales from the North of Israel collects nearly 60 traditional folktales, told mostly by women, that have been carefully translated in the same colloquial style in which they were told. These stories are grouped into themes of love and devotion, ghouls and demons, and animal stories. The work also includes phonetic transcription and linguistic annotation. Accompanying each folktale is a comprehensive ethnographic, folkloristic, and linguistic commentary, placing the tales in context with details on Galilee Bedouin dialects and the tribes themselves. A rich, multifaceted collection, Bedouin Folktales from the North of Israel is an invaluable resource for linguists, folklorists, anthropologists, and any reader interested in a tradition of storytelling handed down through the centuries"--